Sheehan syndrome: Cardiovascular and metabolic comorbidities - Laway, Bashir Ahmad; Baba, Mohammad Salem (Frontiers in Endocrinology, 2023)
Sheehan syndrome (SS) caused by postpartum hemorrhage leads to partial or complete pituitary hormone deficiency. In addition to lipid and glucose abnormalities, patients with SS have increased body fat, insulin resistance (IR), coagulation abnormalities, increased leptin concentration, low-grade inflammation, and endothelial dysfunction that predispose them to cardiovascular diseases. Growth hormone (GH) deficiency, hypogonadism, and excess glucocorticoid use are considered risk factors for these abnormalities. Compared to other hypopituitary subjects, patients with SS are younger and have a longer duration of disease and severe GH deficiency. Replacement with GH in addition to standard hormone replacement improves their cardiometabolic profile.